Amerigo Vespucci : Italian explorer of the Americas - Ray, Kurt. frey50 (New York : Rosen Pub. Group, 2004)
A biography of the Italian-born explorer who was the first person to realize North American was a separate continent.
Ancient questions -- A Florentine family -- The mystery of the letters -- A voyage for Spain -- A voyage for Portugal -- Return to fame.
Keywords: Vespucci, Amerigo, -- 1451-1512; Explorers -- America; Explorers -- Spain; Explorers -- Portugal; Explorers; America -- Discovery and exploration -- Spanish; America -- Discovery and exploration -- Portuguese; America -- Discovery and exploration -- Spanish; America -- Discovery and exploration -- Portuguese .